Interact and engage! : 75+ activities for virtual training, meetings, and webinars - LaBorie, Kassy; Stone, Tom (ATD Press, 2022)
Ignite Online Events and Virtual Training with the Use of Well-Designed and Facilitated Activities Creating outstanding virtual meetings, webinars, and training programs has always been challenging for novice and experienced instructional designers and facilitators alike. Virtual learning experts Kassy LaBorie and Tom Stone understand that the need to interact and engage is more important than ever, as online collaboration becomes the norm rather than the exception. In this new, updated edition of Interact and Engage! , the authors offer more than 75 activities as well as tips and strategies to help you create effective online learning and masterful meetings and webinars. Activities range from warmups and icebreakers to closers and celebrations, and everything in between. LaBorie and Stone cover advanced features and techniques and guide you on how to convert or create your own online activities, no matter what technology you are using now or in the future. An appendix presents two capability models for the positions of virtual facilitator and producer.